2020
DOI: 10.33588/rn.7108.2020381
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la COVID-19 en niños con trastorno del espectro autista

Abstract: Introduction. Children with autism spectrum disorder (ASD) often experience changing routines as a major challenge. For that reason, the need for adaptation during COVID-19 pandemic may have brought major problems to families with children with this pathology. Aim. To explore how children with ASD and their parents experienced the social isolation during COVID-19 outbreak period. Subjects and methods. We conducted an observational, cross-sectional and analytical study. We applied an anonymous questionnaire tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
1
20

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 21 publications
8
97
1
20
Order By: Relevance
“…Despite these differences, which were most penalizing the HR-NDD group, the two groups showed no differences in terms of COVID-19 impact on their emotional and behavioral profiles: effects were not more pronounced on HR-NDD children compared to TD children. This result was contrary to our expectations based on previous studies conducted on children with full-blown diagnosis of NDD [27,32,33,50]. In order to interpret this apparently contrasting finding, it is important to keep in mind that only a restricted proportion of HR-NDD children in our sample had already received a clinical diagnosis (i.e., n = 6 in total, 4 children diagnosed with ASD and 2 children with DLD, respectively, corresponding to 14% of the total HR-NDD group) and were receiving a therapy that was suddenly interrupted and/or switched online.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Despite these differences, which were most penalizing the HR-NDD group, the two groups showed no differences in terms of COVID-19 impact on their emotional and behavioral profiles: effects were not more pronounced on HR-NDD children compared to TD children. This result was contrary to our expectations based on previous studies conducted on children with full-blown diagnosis of NDD [27,32,33,50]. In order to interpret this apparently contrasting finding, it is important to keep in mind that only a restricted proportion of HR-NDD children in our sample had already received a clinical diagnosis (i.e., n = 6 in total, 4 children diagnosed with ASD and 2 children with DLD, respectively, corresponding to 14% of the total HR-NDD group) and were receiving a therapy that was suddenly interrupted and/or switched online.…”
Section: Discussioncontrasting
confidence: 99%
“…In order to interpret this apparently contrasting finding, it is important to keep in mind that only a restricted proportion of HR-NDD children in our sample had already received a clinical diagnosis (i.e., n = 6 in total, 4 children diagnosed with ASD and 2 children with DLD, respectively, corresponding to 14% of the total HR-NDD group) and were receiving a therapy that was suddenly interrupted and/or switched online. It could be hypothesized that discontinuation of face-to-face therapies may be one of the main reasons for the greater vulnerability of children with NDD to emotional and behavioral difficulties during the COVID-19 emergency reported by previous studies [27,32,33,50]. Bentenuto et al [33] have shown that the increase in externalizing behavior in children with NDD was indeed related to a decrease in provided therapies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…So you can imagine that staying at home during quarantine, away from these challenges, can comfort these children. However, in that period, these children had to live with a great stressor for them: the change of routines [30]. For parents with children/young people with ASD, quarantine means not only serving as their child's teacher, but also serving as a special educator, social skills trainer, speech therapist or behavioral/mental therapist, sometimes with little support from professionals [31].…”
Section: Caregivers Of Children With Autism Spectrum Disorder In Thementioning
confidence: 99%
“…Finalmente, Amorim et al (2020) han estudiado el impacto del COVID-19 en niños con TEA. Los resultados muestran que tuvieron un impacto negativo en el manejo de las emociones frente a los niños del grupo de control.…”
Section: Influencia Del Covid-19unclassified